Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas VI Sekolah Dasar dalam Menyelesaikan Soal HOTS Berdasarkan Teori APOS - Armando Bagas Pratama; Nadia Dewi Susianti; Examia Yanuar Rohmah; Amalia Artikasari; Risma Dwi Sabtaningtyas; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
Mathematical problem-solving ability is an essential competency that elementary school students need to develop. However, many students still experience difficulties in solving Higher Order Thinking Skills (HOTS)-based mathematical problems. This study aimed to describe the mathematical problem-solving abilities of sixth-grade elementary school students in solving HOTS-based problems based on the APOS theory. This study employed a descriptive qualitative approach involving five sixth-grade students selected through purposive sampling. Data were collected through a HOTS-based essay test and documentation of students' written work. The data were analyzed using triangulation through data reduction, data display, and conclusion drawing. The findings revealed that most students successfully fulfilled the indicators at the action stage. However, differences in students' abilities were identified at the process and object stages, particularly in determining solution strategies, selecting appropriate concepts and formulas, and connecting mathematical concepts. The schema stage was the most challenging, as most students were unable to obtain correct final answers while simultaneously drawing appropriate conclusions. These findings indicate that APOS theory provides a comprehensive description of students' mathematical problem-solving abilities at each stage of solving HOTS-based mathematical problems.